2021
DOI: 10.3390/app11199232
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Blob Detection for Dental Caries

Abstract: Dental Caries are one of the most prevalent chronic diseases around the globe. Detecting carious lesions is a challenging task. Conventional computer aided diagnosis and detection methods in the past have heavily relied on the visual inspection of teeth. These methods are only effective on large and clearly visible caries on affected teeth. Conventional methods have been limited in performance due to the complex visual characteristics of dental caries images, which consist of hidden or inaccessible lesions. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…They used 11,114 tooth images obtained using data augmentation methods based on periapical dental X-ray images. As a result, the proposed model for caries detection was 97% successful [21]. Vinayahalingam et al carried out a study based on the evaluation of the classification performance of deep learning architectures using panoramic x-ray images.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They used 11,114 tooth images obtained using data augmentation methods based on periapical dental X-ray images. As a result, the proposed model for caries detection was 97% successful [21]. Vinayahalingam et al carried out a study based on the evaluation of the classification performance of deep learning architectures using panoramic x-ray images.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Progression through these stages signifies the extent and severity of decay, highlighting the importance of early detection and intervention . Therefore, there is an urgent need to develop a detection method that is simple, fast, low-cost, and capable of early and precise localization of dental lesion sites. …”
Section: Introductionmentioning
confidence: 99%
“…These parameters include the midline, the length of the upper incisors, the size of the teeth, the various shapes of the incisor teeth, and the way the size, texture, and transitional angles of the teeth look. Other parameters include the midline, the length of the lower incisors, the size of the teeth, and the different shapes of the incisor teeth [4].…”
Section: Introductionmentioning
confidence: 99%
“…The accuracy and classification rate of the results obtained by the four deep learning-adapted techniques are as follows: YOLOV3 (You Only Look Once, Version 3) with 83.4% and 60.7%, quicker R-CNN (Region-based Convolutional Neural Network) with 87.4% and 67.8%, Retinanet with 83% and 65.7%, and lastly SSD with 83% and 68.8% in year 2022. [4] V. Majanga and S. Viriri Automatic Blob Detection for Dental Caries, created a database of 11,114 teeth using dental radiographs by applying a Gaussian blur filter and utilizing erosion and dilation morphology. The study aimed to identify instances of dental caries, and the findings revealed the following information: The value for precision is equivalent to 97%, while the value for the recall is 96% in year 2021.…”
Section: Introductionmentioning
confidence: 99%